PurpleDrop: A Digital Microfluidics-based Platform for Hybrid Molecular-Electronics Applications - Stephenson, Ashley; Willsey, Max; McBride, Jeff; Newman, Sharon; Nguyen, Bichlien; Takahashi, Christopher N; Strauss, Karin; Ceze, Luis (IEEE Micro, 2020)
Molecular manipulation and analysis are the cornerstone of life sciences. With the recent advances in molecular data storage and computing, it has become an increasingly exciting and viable alternative for the post-CMOS scaling era. Widespread use of molecular manipulation/analysis and data storage/computing requires a scalable and low cost platform for hybrid molecular-electronics systems. This enables us to build on the best of what molecular and electronics systems can each offer. In this paper we present PurpleDrop, a full-stack digital microfluidic platform for hybrid molecular-electronic systems in multiple domains, and focus on DNA data storage as a use case. We describe its design principles and relevant aspects such as closed-loop operation with computer vision and capacitive sensing, on-board magnetic bead extraction, and PCR, among other primitives. Importantly, we emphasize the ability to express and execute protocols and computation that include molecular and computational components.